Child Health General Practice Hubs: a service evaluation. Issue 4 (23rd December 2015) - Montgomery-Taylor, Sarah; Watson, Mando; Klaber, Robert
Abstract : Objective: To evaluate the impact of an integrated child health system. Design: Mixed methods service evaluation. Setting and patients: Children, young people and their families registered in Child Health General Practitioner (GP) Hubs where groups of GP practices come together to form 'hubs'. Interventions: Hospital paediatricians and GPs participating in joint clinics and multidisciplinary team (MDT) meetings in GP practices, a component of an 'Inside-Out' change known as 'Connecting Care For Children (CC4C)'. Main outcome measures: Cases seen in clinic or discussed at MDT meetings and their follow-up needs. Hospital Episode data: outpatient and inpatient activity and A&E attendance. Patient-reported experience measures and professionals' feedback. Results: In one hub, 39% of new patient hospital appointments were avoided altogether and a further 42% of appointments were shifted from hospital to GP practice. In addition, there was a 19% decrease in sub-specialty referrals, a 17% reduction in admissions and a 22% decrease in A&E attenders. Smaller hubs running at lower capacity in early stages of implementation had less impact on hospital activity. Patients preferred appointments at the GP practice, gained increased confidence in taking their child to the GP and all respondents said they would recommend the service to family and friends. Professionals valued the improvement in knowledge and learning and, most significantly, the development of trust and collaboration. Conclusions: Child Health GP Hubs increase the connections between secondary and primary care, reduce secondary care usage and receive high patient satisfaction ratings while providing learning for professionals.